Development of water surface mobile garbage collector robot - Kamarudin, Nurul Anis Syahira; Mohd Nordin, Ili Najaa Aimi; Misman, Dalila; Khamis, Nurulaqilla; Muhammad Razif, Muhammad Rusydi; Mohd Noh, Faridah Hanim (2021)
This paper presents a prototype of Water Surface Mobile Garbage Collector Robot built in motivation to educate the people to love and monitor the health of our rivers by collecting the trash themselves using mobile robot. The garbage collector is designed aimed for the cleaning of small-scale lakes, narrow rivers, and drains in Malaysia. The navigation of the robot is controlled using wireless Bluetooth communication from a smartphone application. The performance of the water garbage collector in terms of manoeuvring control efficiency and garbage collection load capacity was tested and evaluated. Based on the experimental results from a swimming pool, it can operate within a 4-metre range and collect 192 grams of small to medium sized recyclable garbage such as food packages, water bottles, and plastics in 10 seconds. It managed to float and navigate on the Panchor River within Bluetooth network range. A strong, lightweight and waterproof material is recommended for use for this water garbage collector. A proximity sensor or image processing technique for detecting garbage on the water surface may be studied and included in the future to enable a fully autonomous manoeuvring control system.